Sistemas de control de erosión en la subestructura de puentes - Monge-Aguilar, Alberto José (Instituto Tecnológico de Costa Rica, 2007)
This Project is in the area of river Hydraulics, giving a solution to a particular problem of erosion at the bridge over the Barranca River. It also attempts to raise conscience of the bridge maintenances necessity. The study of the fluvial principles is developed in ten classic examples for Costa Rica bridges, and it is model in HECRAS. Whit the study of the ten particular cases it is established the basic design parameters: design discharge, flow type, geometric section, the roughness, morphologic and hydraulic, determine the length and the height to protect, the revetment type and the granulometry. With these parameters the solution that works better for the bridge at Barranca River is the articulating concrete blocks
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2007.
Keywords: Hidráulica; Conciencia social; Sistemas articulados; Factores erosivos; Topografía